(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2010)
The aim of this work is to study the effect of the following parameters :reduction in thickness , length of contact, rolling radius, viscosity of lubricant oil, and roll speed on the lubricant film thickness which are pointed to as an independent variables. In order to illustrate the effect of these parameters, three types of lubricants ,A( Commercial rolling oil, known as Roll oil 981), B ( Forming cutting oil called Exx cut 225, with additive ) and C (Forming cutting oil called Exx cut 225 ). Were selected also three values for roll radius (55,65,and 75 mm), with three values for roll velocities (0.5, 1, and 1.5 m/s), and finally five values for reduction in thickness (75, 80, 85, 90, and 95%) were examined to cover all inquires in this work. The study shown that an increase in roll radius leads to increase in lubricant film thickness . At high reduction, the lubricant film thickness becomes very small, and requires the use of high viscosity lubricant.